Vascularization of Head and Neck Paragangliomas: Comparison of Three MR Angiographic Techniques with Digital Subtraction Angiography - van den Berg, René (AJNR Am J Neuroradiol, 2000)
BACKGROUND AND PURPOSE: MR angiography of the head and neck region has been studied widely, but few studies have been performed concerning the efficacy of MR angiography for the identification of the specific vascular supply of the highly vascular head and neck paragangliomas. In this study, we compared three MR angiography techniques with respect to visualization of branch arteries in the neck and identification of tumor feeders in patients with paragangliomas. METHODS: Fourteen patients with 29 paragangliomas were examined at 1.5 T using 3D phase-contrast (PC), 2D time-of-flight (2D TOF), and multi-slab 3D TOF MR angiography. In the first part of the study, two radiologists independently evaluated the visibility of first-, second-, and third-order branch arteries in the neck. In the second part of the study, the number of feeding arteries for every paraganglioma was determined and compared with digital subtraction angiography (DSA), the standard of reference in this study. RESULTS: Three-dimensional TOF angiography was superior to the other MR angiography techniques studied (P < .05) for depicting branch arteries of the external carotid artery in the neck, but only first- and second-order vessels were reliably shown. DSA showed a total of 78 feeding arteries in the group of patients with 29 paragangliomas, which was superior to what was revealed by all MR angiography techniques studied. More tumor feeders were identified with 3D TOF and 2D TOF angiography than with 3D PC MR angiography (P < .05), with a sensitivity/specificity of 61%/98%, 54%/95%, and 31%/ 95%, respectively. Sensitivity was lowest for carotid body tumors. CONCLUSION: Compared with intra-arterial DSA, the 3D TOF MR angiography technique was superior to 3D PC and 2D TOF MR angiography for identifying the first- and second-order vessels in the neck. With 3D TOF angiography, more tumor feeders were identified than with the other MR angiography techniques studied. The sensitivity of MR angiography, however, is not high enough to reveal important vascularization. The sensitivity of MR angiography is too low to replace DSA, especially in the presence of carotid body tumors.